2022
DOI: 10.1002/anie.202116406
|View full text |Cite|
|
Sign up to set email alerts
|

Isoselective Hydroformylation of Propylene by Iodide‐Assisted Palladium Catalysis

Abstract: Isobutanal is a high value bulk material that, in principle, could be produced with 100 % atom‐economy by isoselective hydroformylation of propylene with syngas. However, leading industrial Rh‐ and Co‐catalyzed hydroformylation methods preferentially form n‐butanal over the iso‐product, and methods offering isoselectivity remain underdeveloped. Here we report an iodide‐assisted Pd‐catalyzed hydroformylation of propylene that produces isobutanal with unprecedented levels of selectivity. The method involves PdI2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We believe that converter gas can be used for many other atom- and step-economical reduction transformations in the near future. In particular, converter gas from steel plants might replace natural gas sources in well-known large-scale industrial processes involving CO such as synthesis of acetic acid, 36–38 hydroformylation, 39–41 urea synthesis, 8,42–44 etc. Hopefully, this discovery will attract other researchers to develop chemical processes involving converter gas.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that converter gas can be used for many other atom- and step-economical reduction transformations in the near future. In particular, converter gas from steel plants might replace natural gas sources in well-known large-scale industrial processes involving CO such as synthesis of acetic acid, 36–38 hydroformylation, 39–41 urea synthesis, 8,42–44 etc. Hopefully, this discovery will attract other researchers to develop chemical processes involving converter gas.…”
Section: Discussionmentioning
confidence: 99%
“…42 Recently, Dydio and co-workers showed the relevance of phosphine stereoelectronics in achieving a rare iso-selective hydroformylation of propylene. 43 Using Pd Vaska-type complexes, 44 they found that cone angle of between 152–178° and a TEP below 2060 cm −1 was crucial to achieving active catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…the classic mononuclear catalytic cycle (rather than a binuclear mechanism as concluded in our mechanistic studies). 12…”
Section: Synpacts Synlettmentioning
confidence: 99%
“…37 The observed effect was proposed to originate from the halide-assisted heterolytic splitting of dihydrogen, which facilitates the hydrogenolysis of the Pd–acyl species within the classic mononuclear catalytic cycle (rather than a binuclear mechanism as concluded in our mechanistic studies). 12…”
Section: Pd-catalyzed Isoselective Hydroformylation Of Unbiased Aliph...mentioning
confidence: 99%
See 1 more Smart Citation